2000
DOI: 10.1007/bf02682262
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CD95 on peripheral blood lymphocytes in patients with autoimmune diseases and neoplasms

Abstract: CD95 expression on peripheral blood lymphocytes in patients with neoplasms was higher than in patients with autoimmune disorders. Apoptosis of T cells increased during tumor growth. The data suggest that neoplasms are accompanied by more severe immune dysfunction than autoimmune disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
1
0
0
Order By: Relevance
“…Our results seem to be in agreement with the idea of SLE as a disease with chronic immune system activation, which means that the more cells express late-activity markers (CD95 and HLA-DR) [12,23] in association with higher disease activity, whereas the expression of CD69 (the marker of early stages of cell activation in SLE) and CD25 int (the middle activity marker) occurs only in the first stages of SLE patients with higher disease activity [24] and is not chronically expressed on the T cell surface. At first glance these results seem to be opposite those presented by GÔmez-MartÎn et al [25], who reported that the immunosuppressive drug Azathioprine decreases the level of CD4 ϩ CD69 ϩ and CD4 ϩ CD25 high cells.…”
Section: Figsupporting
confidence: 92%
“…Our results seem to be in agreement with the idea of SLE as a disease with chronic immune system activation, which means that the more cells express late-activity markers (CD95 and HLA-DR) [12,23] in association with higher disease activity, whereas the expression of CD69 (the marker of early stages of cell activation in SLE) and CD25 int (the middle activity marker) occurs only in the first stages of SLE patients with higher disease activity [24] and is not chronically expressed on the T cell surface. At first glance these results seem to be opposite those presented by GÔmez-MartÎn et al [25], who reported that the immunosuppressive drug Azathioprine decreases the level of CD4 ϩ CD69 ϩ and CD4 ϩ CD25 high cells.…”
Section: Figsupporting
confidence: 92%